Identity strategies in light of a low-prestige occupation: the case of retail apprentices - Duemmler, Kerstin [Verfasser]; Caprani, Isabelle [Verfasser] (My University, 2017)
"Occupations differ in their prestige, but little research has examined how workers manage working in a low-prestige occupation. This case study with retail-clerk apprentices in Switzerland uncovers the identity strategies the apprentices employ to help them normalise the situation they find themselves in: they are learning an occupation that is not assumed to require any specific knowledge or skills. We base our arguments on theories about occupational prestige, identity and stigma management, as well as on a qualitative study in VET (vocational education and training) schools. Three identity strategies are dominant among retail-clerk apprentices and are deeply embedded within the retail context and the Swiss apprenticeship programme. First, apprentices embrace ideas of discontinuous careers and lifelong learning, which encourage them to improve their occupational position through mobility within or outside the retail sector. Second, the VET programme builds on apprentices' consumer interests and encourages their self-valorisation through the prestige of products and shops. Third, apprentices emphasise that retail work is skilled work, a strategy that is consistent with the positive societal perception of the Swiss VET system. These strategies provide insights into how apprentices construct positive occupational identities although they are placed low on the occupational prestige hierarchy." (Authors' abstract; BIBB-Doku)
Keywords: S 6.4.1 Kaufleute; P 2.3 Auszubildende; G 2.4.4 Biografiegestaltung; Kaufmännischer Beruf; Kaufmann im Einzelhandel; Auszubildender; Berufliche Identität; Berufsprestige; Berufliche Sozialisation; Schweiz